Research of network hydraulics for pumping station - untreated water line system (PVC-P - Koral, Wojciech (Instal, 2021)
The paper shows the results of research in resistance coefficient of untreated water line made of PVC and PE, causing a significant reduction of pumping station capacity supplying, as a primary source, a water treatment plant for a town with several thousand inhabitants in western Poland.